2020
DOI: 10.1111/cxo.12917
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and deterrents for seeking eye care in a Canadian region

Abstract: Background Motivators and deterrents for seeking eye care in a Canadian setting were sought using a qualitative study. Provincial deregulation of eyewear dispensing in 2010 allows consumers to order eyewear without an optical prescription, thus eliminating a potential motivator for obtaining an eye examination. Methods Convenience sampling was used to obtain 25 members of the public who contributed to one of seven focus groups that were facilitated, audiotaped, anonymised and transcribed. Participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The appeal of inexpensive eyewear is not surprising considering the results of previous research identifying high cost (and lack of insurance) as barriers to regular eye care 13 . The ACLM survey 11 found that 91% of respondents cited price as the reason for online purchasing of contact lenses.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The appeal of inexpensive eyewear is not surprising considering the results of previous research identifying high cost (and lack of insurance) as barriers to regular eye care 13 . The ACLM survey 11 found that 91% of respondents cited price as the reason for online purchasing of contact lenses.…”
Section: Discussionmentioning
confidence: 98%
“…The appeal of inexpensive eyewear is not surprising considering the results of previous research identifying high cost (and lack of insurance) as barriers to regular eye care. 13 The ACLM survey 11 found that 91% of respondents cited price as the reason for online purchasing of contact lenses. Similarly, optimising convenience (41% in the ACLM contact lens survey 11 ) has been cited as a draw for consumers in research dating from the 1960s, decades before the rise of e-commerce.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations